DETERMINANTS OF STUDENT SATISFACTION IN NON-FORMAL MANDARIN LANGUAGE COURSES - Lisa Lisa; Auditia Setiobudi (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
This inquiry explores the specific elements driving student fulfillment within the landscape of non-formal Mandarin education in Surabaya, with a primary lens on service quality, instructor quality, and administrative support. Given the surging popularity of Mandarin proficiency, educational centers face heightened rivalry, positioning student satisfaction as a vital benchmark for institutional efficacy and academic success. Utilizing a quantitative framework, the study gathered insights from 58 individuals who engaged in Mandarin programs over the preceding year. Through multiple linear regression, the research analyzed how independent factors—individually and collectively—shape the student experience. The empirical evidence reveals that both service quality and instructor quality exert a meaningful, positive impact on satisfaction levels, with the instructor’s performance emerging as the primary catalyst. Conversely, while administrative support correlates positively with satisfaction, its statistical significance remains marginal, indicating its role is foundational rather than a primary driver. These outcomes underscore the necessity for institutions to prioritize teaching standards and consistent service output to bolster student loyalty, while maintaining administrative efficiency to facilitate the broader learning journey.